The Existence of Palang Pintu Culture in the Opening Procession of Betawi Traditional Weddings (Case Study: George Herbert Mead's Symbolic Interactionism) - Sari Tri Anjani; Iskandarsyah Siregar (Formosa Journal of Sustainable Research, 2022)
This study analyzes how the existence of Palang Pintu Betawi culture and the understanding of the meaning of using Palang Pintu in Betawi traditional weddings. The purpose of this research is to look for strategies for restoring the Betawi traditional Palang Pintu culture. The theory used is George Herbert Mead's symbolic interaction theory. The method used in this study is the qualitative research method of Cresswell, J.W. The nature of this research is descriptive. By using the questionnaire method as data collection. The results obtained are an explanation of how the existence of Palang Pintu culture as an opening in the Betawi traditional event. As well as what strategies can be implemented to restore the Betawi culture which is almost extinct